Effect of students' subject areas on psycho-cognitive outcomes in mathematics (2007)
This study examined the 'effect of Students' Subject Specializations on their Psycho-Cognitive outcomes '. Three hundred andfour students selected through purposive sampling using homogeneous approach needs than other students. The commercial students were found constituted the sample for the study. They provided data on their subject areas, psychological and cognitive outcomes in mathematics. The data collected was analyzed using ANOVA and Post hoc test (multiple comparison) to test the significance of the differences at the 0.05 level of significance. All the null hypotheses were rejected. The cognitive, ego-enhancing, and affiliative needs as well as achievement of students in mathematics were found to be significantly affected by their subject areas. Also, science students were found to have higher cognitive and ego-enhancing to be better in affiliative needs and academic achievement in mathematics than science and art students Based on the findings of this study, it is recommended that apart from classroom teaching, mathematics teachers should organize various mathematics oriented activities that will boost cognitive, ego-enhancing and affiliative needs of their students